Irradiation of Anastrepha fraterculus (Diptera: Tephritidae) Eggs to Inhibit Fly Emergence in the Mass-Rearing of Diachasmimorpha longicaudata (Hymenoptera: Braconidae). Issue 1 (25th August 2016) - Costa, M. L. Z.; Pacheco, M. G.; Lopes, L. A.; Botteon, V. W.; Mastrangelo, T.
Abstract: As the incidence of Anastrepha fraterculus (Wiedemann) has increased in Southern Brazil in the past 3 yr, an initiative to release sterile flies and parasitoids has started. In order to make feasible the mass-rearing of the parasitoid Diachasmimorpha longicaudata (Ashmed), this study investigated the suitability of A. fraterculus larvae derived from irradiated eggs as host for D. longicaudata . Two different ages of A. fraterculus eggs (24 and 48 h old) were analyzed for hatchability after the exposure to a range of radiation doses. The hatchability of 48-h-old eggs was not affected by radiation, and no fly emerged at doses higher than 27.5 Gy. The larvae derived from irradiated eggs proved to be suitable hosts for the parasitoid development, with observed parasitism rates higher than 70% and sex ratio values above 0.6. The parasitism capability and longevity of D. longicaudata reared on larvae derived from irradiated eggs were also assessed. During the 10 d of parasitism evaluated, D. longicaudata from the treatments were able to parasitize nonirradiated larvae similarly as the parasitoids from controls and the laboratory colony. The longevity of D. longicaudata from the treatments was not affected either, with survival rates higher than 80% after 20 d of evaluation. The age of 48 h and a dose of 30 Gy could be considered the best age and dose for A. fraterculus eggs to be used in the mass-rearing of D. longicaudata . The results of this study will decrease the costs of mass-rearing D. longicaudata on A. fraterculus .